Chemotaxonomy of the ethnic antidote Aristolochia indica for aristolochic acid content: Implications of anti-phospholipase activity and genotoxicity study. (10th February 2021) - Dey, Abhijit; Hazra, Alok Kumar; Mukherjee, Anuradha; Nandy, Samapika; Pandey, Devendra Kumar
Abstract: Ethnopharmacological relevance: Aristolochia indica L. (Aristolochiaceae) is a common medicinal plant described in many traditional medicine as well as in Ayurveda used against snakebites. Besides, the plant has also been reported traditionally against fever, rheumatic arthritis, madness, liver ailments, dyspepsia, oedema, leishmaniasis, leprosy, dysmenorrhoea, sexual diseases etc. The plant is known to contain its major bioactive constituent aristolochic acid (AA) known for its anti-snake venom, abortifacient, antimicrobial and antioxidant properties. Materials and methods: This present work describes a validated, fast and reproducible high performance thin layer chromatography (HPTLC) method to estimate AA from the roots of 20 chemotypes of A. indica procured from 20 diverse geographical locations from the state of West Bengal, India. Further, an evidence-based approach was adopted to investigate the reported anti-venom activity of the aqueous extracts of the A. indica roots by assessing its phospholipase A2 (PLA2 ) inhibitory properties since PLA2 is a major component of many snake-venoms. Finally, the cytotoxicity and genotoxicity of the aqueous root extract of the Purulia (AI 1) chemotype were assessed at various concentrations using Allium cepa root meristematic cells. Results: The highest amount of AA (7643.67 μg/g) was determined in the roots of A. indica chemotype collected from Purulia district followed by the chemotypes collected from Murshidabad, Jalpaiguri and Birbhum districts (7398.34, 7345.09 and 6809.97 μg/g respectively). This study not only determines AA in the plants to select pharmacologically elite chemotypes of A. indica, but it also identifies high AA producing A. indica for further domestication and propagation of the plants for pharmacological and industrial applications. The method was validated via analyzing inter-day and intra-day precision, repeatability, reproducibility, instrumental precision, limit of detection (LOD) and limit of quantification (LOQ) and specificity. Chemotypes with high AA content exhibited superior anti-PLA2 activity by selectively inhibiting human-group PLA2 . Moreover, A. indica root extract significantly inhibited mitosis in Allium cepa root tips as a potent clastogen. Conclusions: The present quick, reproducible and validated HPTLC method provides an easy tool to determine AA in natural A. indica plant populations as well as in food and dietary supplements, a potential antivenin at one hand and a possible cause of aristolochic acid nephropathy (AAN) at another. Besides, the cytotoxic and mitotoxic properties of the root extracts should be used with caution especially for oral administration. Graphical abstract: Image 1 Highlights: Chemical variation is attributed to geographical locations for Aristolochia indica . Aristolochic acid is analyzed in chemotypes of A. indica using chromatography. Elite chemotypes may further be exploited for commercial and industrial use. Anti-phospholipase A2 activity of the root extract was analyzed. Genotoxicity test was performed on the root extract using Allium cepa root tip assay.